Efeitos de concentrações crescentes de glicerol sobre a atividade da n-acetil glicosaminidase - Garrote Filho, Mario da Silva (2008)
Experiments performed with the enzyme N-acetyl-β-D-glucosaminidase (NAGase), secreted by the fungus Trichoderma harzianum, reveal that glycerol concentrations of 0,5 and 1,0 mol.L-1 increase the enzyme activity until a maximum value. Between 1,5 and 2,0 mol.L-1, glycerol decreases the enzyme activity. This effect was observed at different temperatures of the interval between 30 and 70 °C and also in the presence of increasing urea concentrations until 2,0 mol.L-1. The decrease in enzyme activity was larger in the presence of urea and glycerol than solely in the presence of urea. A model based in the concepts of microstates and ensembles was elaborated to explain the glycerol behavior.